Major Depressive Disorder in the adolescent – barriers to managing adolescent mental health problems at primary care - Abdullah, Fa’iza; Kamaluzaman, Qamarul Azwan; Yatim, Yusnita; Mat Nor, Mohd Basri (Zes Rokman Resources, 2023)
Major Depressive Disorder (MDD) among adolescents is an important health problem among adolescents and leads to high-risk behaviours and suicide. Given the increasing prevalence of MDD among adolescents, early identification is vital for immediate intervention. The primary care team is an important intermediator in managing MDD, whereby parents and school officials play pivotal roles in achieving optimum recovery. This case report aims to acknowledge the importance of biopsychosocial support and unveil the barriers faced in managing adolescent MDD in primary care. This was a case of a female adolescent aged 14 years old, diagnosed with MDD after a comprehensive psychological assessment. She had previously visited the clinic several times for other acute problems before MDD was diagnosed. She has been co-managed by primary care and hospital psychiatry clinic specialists. Her initial management included two weekly clinic follow-ups for clinical monitoring and counselling sessions with trivial improvement. Her mental health condition was significantly improved after an intensive approach comprising patient-family counselling, school visits, patient self-empowerment, and hospital follow-ups for psychotherapy sessions. Furthermore, her mood improved, evident in her interest in daily activities and focus on classes. Despite the busy schedules of primary care doctors, a high commitment is required for the successful management of MDD in adolescents and overcoming its challenges. Primary care plays an important role in employing a multidisciplinary team approach to coordinate care with the family and school and improve psychosocial support and peer group acceptance. Barriers could be addressed to catalyse the diagnostic process, reduce personal and social stigma, and enhance self-empowerment and compliance in achieving the most favourable care and recovery.